Guardians of Public Value
XIII, 353 p. 9 illus., 4 illus. in color.
Keywords: This open access book presents case studies of twelve organisations which the public have come to view as institutions. From the BBC to Doctors Without Borders, from the Amsterdam Concertgebouw Orchestra to CERN, this volume examines how some organisations rise to prominence and remain in high public esteem through changing and challenging times. It builds upon the scholarly tradition of institutional scholarship pioneered by Philip Selznick, and highlights common themes in the stories of these highly diverse organizations; demonstrating how leadership, learning, and luck all play a role in becoming and remaining an institution. This case study format makes this volume ideal for classroom use and practitioners alike. In an era where public institutions are increasingly under threat, this volume offers concrete lessons for contemporary organisation leaders. Arjen Boin is Professor of Public Institutions and Governance at the Department of Political Science, LeidenUniversity, Netherlands. Paul ‘t Hart is Professor of Public Administration at the Utrecht School of Governance, Utrecht University, Netherlands. Lauren A. Fahy is a PhD Fellow at the Utrecht School of Governance, Utrecht University, Netherlands.